Key access and utilization descriptors for cowpea genetic resources - Bioversity International; National Bureau of Plant Genetic Resources; International Institute of Tropical Agriculture (2010)
This minimum list consists of an initial set of characterization and evaluation descriptors for cowpea utilization. This strategic set of descriptors, together with passport data, will become the basis for the global accession level information portal being developed by Bioversity International with the financial support of the Global Crop Diversity Trust (GCDT). It will facilitate access to and utilization of cowpea accessions held in genebanks and does not preclude the addition of further descriptors, should data subsequently become available. Biotic stresses included in the list were chosen because of their cosmopolitan nature, wide geographical occurrence and significant economic impact.